2022
DOI: 10.1111/jgh.15847
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric injection of botulinum toxin A for weight loss: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Background and Aim: Intragastric botulinum toxin A (BTA) injection is a potential treatment for weight reduction in obese patients. Current studies yielded conflicting results. We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the efficacy of intragastric BTA injection for weight management. Methods: We searched several databases to identify RCTs evaluating intragastric BTA injections for obesity. We applied random-effects models for all meta-analyses due to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
(116 reference statements)
0
11
0
Order By: Relevance
“…The cause of the severe adverse effects in the reported cases remains speculative. Yen et al reviewed six RCTs with 192 cases and identified doses of ≥200 MU Ona‐BoNT/A or Inco‐BoNT/A as adequate and safe for the intragastric injection, with the highest reported dose being 500 MU in one trial [1]. In our patients, 1500 MU of Abo‐BoNT/A had been applied.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The cause of the severe adverse effects in the reported cases remains speculative. Yen et al reviewed six RCTs with 192 cases and identified doses of ≥200 MU Ona‐BoNT/A or Inco‐BoNT/A as adequate and safe for the intragastric injection, with the highest reported dose being 500 MU in one trial [1]. In our patients, 1500 MU of Abo‐BoNT/A had been applied.…”
Section: Discussionmentioning
confidence: 89%
“…However, not all eligible patients decide to undergo this invasive procedure. Endoscopic intragastric injection of botulinum neurotoxin A (BoNT/A) was proposed as an alternative obesity treatment, achieving weight loss by delayed gastric emptying and speeded satiety [1]. However, this approach lacks authorization by the European Medicines Agency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGBI doses ranged from 100 units to 500 units and were administered to the antrum; antrum and body; or antrum, body, and fundus of the stomach for a total tracked period from 5 to 24 weeks. In the five RCT groups, the percent of weight loss ranged from 4.9% to 9.0%, indicating that IGBI was effective [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review and meta-analysis, IGBI in adequate doses (≥ 200 U) and multiple injections across the gastric various regions, was found to be effective in reducing weight when combined with diet control. [ 3 ] The exact mechanism for weight loss is unclear but is believed to be related to prolonging gastric half-emptying time.…”
mentioning
confidence: 99%